The development of the agricultural newspaper - Harlan, Harry Vaughn (My University, 1904)
Introduction: The Agricultural press comes in the division known as special or class journalism. The cause of the foundation of an agricultural press is the same as with all other special publications. There is always a demand before such a journal is founded. We often hear the statement that the mission of the agricultural paper is to educate the farmers, but we may feel sure that no one has taken such a duty upon himself until the farmer has desired to be educated. Of course the first press notices pretaining to agriculture were found in journals of a general and not agricultural nature.
Citation: Harlan, Harry Vaughn. The development of the agricultural newspaper. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Agricultural Newspapers; Agriculture; Communication; Media; Theses